Meningkatkan Minat Belajar Siswa dengan Variasi Belajar Audio Visual dan Interaktif - Nadila Ardhia Garini; Fajar Utama Ritonga; Hairani Siregar (Yayasan Literasi Sains Indonesia, 2023)
Low student interest in learning is a challenge in this 4.0 technology era. Technological stuttering accompanied by self-doubt makes it difficult for students to progress and keep up with the times. Coupled with learning that is too monotonous, it makes students' interest in learning even lower. There is a Teaching Campus MBKM (Freedom Learning Campus) program that can help overcome the obstacles that exist in various schools in Indonesia. The author here was moved to take part in the program and found a problem where the learning system was monotonous, which made students' interest in learning, which was initially low, grow lower. In this study, the authors used the Groupwork Method with stages such as: (1) Engagement, Intake and Contract, (2) Assessment, (3) Planning, (4) Intervention, (5) Monitoring, (6) Evaluation, and (7) Termination. The purpose of this study is to increase students' interest in learning through audio-visual learning variations such as the use of technology and interactive learning variations so as to increase students' sense of courage and confidence. The results of this research show that students' interest in learning has increased and students are more daring to show themselves and have self-confidence.